2016
DOI: 10.1097/prs.0000000000002173
|View full text |Cite
|
Sign up to set email alerts
|

Revisions in Implant-Based Breast Reconstruction: How Does Direct-to-Implant Measure Up?

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 21 publications
3
40
2
1
Order By: Relevance
“…Indeed, similar findings have been seen in some previous studies (e.g. [27,28]). In brief, the scientific evidence for the hypothesis that meshes give a lower capsular frequency is still weak and not supported by our study.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, similar findings have been seen in some previous studies (e.g. [27,28]). In brief, the scientific evidence for the hypothesis that meshes give a lower capsular frequency is still weak and not supported by our study.…”
Section: Discussionsupporting
confidence: 92%
“…It is possible to place the implant in either the dual plane under the pectoralis superiorly and supported inferiorly by an ADM sling or in the subcutaneous plane. 47,50,51 A known requirement for postmastectomy radiation therapy is a relative contraindication for single-stage breast reconstruction, regardless of the plane; therefore, there are very few studies commenting on radiation in direct-to-implant reconstruction. Using a twostage approach is thought to be safer and allows additional opportunities to thwart radiation-related capsular contracture and malposition, by overexpanding or adjunctive techniques performed at the time of the implant exchange.…”
Section: Radiation In Direct-to-implant Reconstructionmentioning
confidence: 99%
“…50 Clarke-Pearson et al found that radiation was predictive of capsular contracture and reoperation for revision in single-stage reconstructions. 51 If the requirement for postmastectomy radiation therapy is known preoperatively or highly suspected, reconstruction should be performed using two stages to optimize aesthetic results and minimize complications.…”
Section: Radiation In Direct-to-implant Reconstructionmentioning
confidence: 99%
“…The difference in revision rates between the prophylactic breast and the diseased breast was no longer significant when adjusting for all confounding variables in the penalized regression model. Nevertheless, the revision rates of this study compare favorably with previously published revision rates for immediate implant-based reconstruction [57,85]. In addition to overall postoperative outcomes, we were also interested in determining whether certain outcomes were influenced by specific treatments or risk factors.…”
Section: Discussionmentioning
confidence: 58%
“…For example, if a patient underwent lumpectomy with sentinel lymph node biopsy and then proceeded with a completion mastectomy, we included them in the sentinel lymph node biopsy group. Mastectomies and reconstructions were performed as previously described by our group [53][54][55][56][57]. Evaluation of the post-mastectomy flap thickness, skin color, and capillary refill was coupled with patient risk factors and the surgeon experience to determine final candidacy for the type of mastectomy and reconstruction.…”
Section: Data Collectionmentioning
confidence: 99%